Rationalising Transgression - Tracy Flenady; Trudy Dwyer; Judith Applegarth (Grounded Theory Review: An International Journal, 2016)
The aim of this classic grounded theory study was to unearth the main concern of emergency department (ED) registered nurses (RN) when they perform respiratory rate observations to generate a substantive theory that explicates how the identified problem is resolved. Analysis of data collected from 79 registered nurses revealed that health sector forced compliance in recording observations meant that ED RNs are more than likely to record a respiratory rate without actually counting respirations. This erroneous behaviour provokes varying degrees of emotional discomfort as the nurses’ actions are often incongruent with their professional values and beliefs. The theory Rationalising Transgression explains how nurses continually resolve this issue by compensating, minimalizing, or trivialising to titrate the level of emotional discomfort associated with erroneous behaviour, consequently facilitating the rationalisation of transgression.